COVID 19: Political, Security and Religious Impacts on Nigerian Children - Al-Khateeb, Abdulqader; Amuda, Yusuff Jelili (Journal of Ecohumanism, 2024)
It is unfortunate that corruption and insecurity have affected all spheres of human endeavours in Nigeria. The recent outbreak of Covid-19 otherwise known as coronavirus has created a vacuum regarding its effects on the lives of the citizens in general and children in particular. The prime focus of this paper is to explore the political, security and religious impacts of Covid-19 specifically on the children. This paper analyzes the aforementioned factors of Covid-19 in connection with children as to address injustice against children in the country. This is necessary because children used to be given less attention in political decisions and many of them have been affected as a result of insecurity in different parts of the country. Hence, addressing various factors relating to Covid-19 explored in this paper may be instrumental in helping the children as minors as many international agencies have been trying to solve it. It is therefore suggested that various issues are addressed so that safety can be provided to the children by alienating the multifarious impacts of Covid-19 in the country.